"Valve in valve" implantation of two self‐expandable transcatheter aortic valves in a patient with aortic root aneurysm and massive aortic regurgitation: "A new TAVI option". Issue 5 (23rd October 2013) - Pesarini, Gabriele; Bedogni, Francesco; Ribichini, Flavio
<x xml:space="preserve">Abstract</x> Catheter‐based treatment of aortic regurgitation (AR) often proves challenging especially due to associated anatomical difficulties. Here, we present a case of CoreValve implantation with a novel use of the valve‐in‐valve technique to effectively treat severe AR in a patient with repeated cardiac surgery and aneurismatic prosthetic ascending aorta. © 2013 Wiley Periodicals, Inc.